Storage Stability of Arauco Virgin Olive Oil: Evolution of Its Quality Parameters and Phenolic and Triterpenic Compounds under Different Conservation Conditions - Monasterio, Romina Paula; Trentacoste, Eduardo Rafael; López Appiolaza, Carlos; Beiro-Valenzuela, María Gemma; Serrano-García, Irene; Olmo-García, Lucía; Carrasco-Pancorbo, Alegría (MDPI, 2023)
The storage conditions are very critical to minimize hydrolytic and oxidative reactions of virgin olive oils (VOOs). These reactions are logically influenced by the composition of the VOO, so that each variety may have a specific behavior. The aim of this study was to evaluate changes in quality parameters and in the phenolic and triterpenic profile of Arauco VOOs, a unique local variety from Argentina, after storage under different conditions. The effects of exposure to light (darkness and light), temperature (24 and 40 °C), packaging material (polyethylene (PET) and dark glass), and headspace (air and N2 atmosphere) were investigated for 76 days. A reduction in total phenolic compounds was observed after storage treatments, but all samples still complied with the EFSA health claim after the different handlings. Overall, the results revealed that the preservation of the oils in PET appears adequate, with improved stability when N2 was used in the headspace, along with darkness and low temperature. The study of phenolic profiles showed that substances previously reported as possible markers of olive oil aging, such as hydroxytyrosol and an isomer of decarboxymethyl oleuropein aglycone, also have a similar behavior during the aging of Arauco variety oil. Interestingly, some evidence was found that another oleuropein-derived compound (oleuropein aglycone isomer 3) could also be used as an aging marker.